Calix[4]arene‐Based Dynamic Covalent Gels: Marriage of Robustness, Responsiveness, and Self‐Healing. Issue 4 (18th December 2017) - Yang, Hui; Tang, Jiaqi; Shang, Congdi; Miao, Rong; Zhang, Shaofei; Liu, Kaiqiang; Fang, Yu
Abstract: Herein, the report on a new class of self‐healing and pH/temperature responsive mixed solvent (ethanol and water) gels shows unusual mechanical properties to resist slicing, sustain high compression, and withstand stretching as evidenced by the cutting breaking stress, the fracture compressive stress, and the stretching ratio of one of the gels as obtained can reach or exceed 26.4 MPa, 9.2 MPa, and ≈5 times, respectively. The gels are designed by introducing dynamic covalent bond, acylhydrazone, which is believed to combine the merits of conventional chemical bonds and those of supramolecular interactions. Specifically, a hydrazide‐modified calix[4]arene derivative and linear benzaldehyde‐terminated poly(ethylene glycol)s are synthesized and used as reactive components to build gel networks. Interestingly, acid‐degradable hydrogel can be obtained via natural drying of the mixed solvent gel first and then swelling in pure water. Abstract : New kinds of self‐healing and pH/temperature responsive dynamic covalent gels are synthesized via reaction between a hydrazide‐modified calix[4]arene derivative and benzaldehyde‐terminated poly(ethylene glycol)s in suitable solvents. Interestingly, the gels show unusual mechanical properties, such as resisting slicing, sustaining compression, and withstanding stretching.